Bureaucracy and Education: an analysis since Max Weber - Melo Júnior, João Alfredo Costa de Campos (Pensamento Plural, 2010)
This paper aims at providing a discussion on bureaucracy and education based on the comprehensive sociology developed by Weber. The choice of Max Weber seems to be the most appropriate due the diversity and depth of his intellectual production, what includes the issue of bureaucracy. The use of Weber should serve as a precise instrument of conceptual analysis on the theme addressed here. Certainly, this thinker has been one of the main scholars on bureaucracy, with focus on Germany at the time of the First World War (1914-1918). It is within such a productive theoretical framework that we intend to provide a few reflections about education and bureaucracy from a Weberian epistemological base.

Cabe a este texto elaborar uma reflexão acerca da burocracia e da educação, tendo como princípio norteador a sociologia compreensiva weberiana. A opção por Max Weber se revela a mais acertada devido à diversidade e à profundidade de sua produção intelectual, incluindo a questão da burocracia. A utilização de Weber servirá como instrumento preciso de análise conceitual sobre a temática aqui proposta. Certamente, o pensador foi um dos principais estudiosos da burocracia, tendo como palco privilegiado a Alemanha na época da Primeira Grande Guerra (1914-1918). É dentro desse fecundo arcabouço teórico que se pretende fazer algumas incursões sobre a educação e a burocracia, tendo com respaldo epistemológico Weber.
Keywords: Bureaucracy; Education; Max Weber; Sociological Theory